H E R M E N E U T I K A Sebuah Teori Lama Mengenai Interpretasi Teks yang Tampak Baru - Purwito Purwito (Institut Seni Indonesia Yogyakarta, 2012)
Hermeneutics as an object of study is a means of understanding the ”actual” as old ashuman beings age on this earth. Hermeneutics is very important in the process of humaninteraction, so the study was conducted to study the hermeneutics in his position as a scienceof interpretation that can be studied in ontological, epistemological, and axiological. As ascience, hermeneutics emerged as a dominant movement in European Protestant theologywhich states that hermeneutics is a focal point of the current theological issues.Associated with his position as a science, the study was conducted to determinehermeneutics in the concept of etymology and terminology, knowing on historically with thefigures who pioneered the science of it, his position as a theory of interpretationmultidisciplinary, as well as the position and function as a historiographical approach throughphilological approach.Keywords: hermeneutics, the theory of interpretation, and text.